MANAJEMEN RISIKO OPERASIONAL PADA LEMBAGA AMIL ZAKAT NASIONAL - Muhammad Fitrahuddin Ajmal Nazir; Muhammad Nafik Hadi Ryandono (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
The purpose of this study is to know how the national zakat institution manage their operational risk. Things that needs to be reviewed in the operational risk management based on the phenomenon that occurs in the research objects. The objects of this research is three national zakat institution with head office in Surabaya, which three national zakat institution is Yatim Mandiri, Nurul Hayat and YDSF. This research uses qualitative method with case study approach. After the interview, the results of the study were analyzed using descriptive data analysis techniques. The results of research conducted by researchers to three respondents, that operational risk management already performed by three national zakat institution based on their own way. There are 14 risks that identified. How the national zakat institution manage their risks depends on experiences of each national zakat institution itself.Keywords: Risk, Zakat, Operational Risk Management, National Zakat Institution